Monitoring of Icelandic plate movement with GNSS method and GPS signal jamming effects in Iceland - Pirti, Atinc; Hosbas, Ramazan Gursel; Yucel, Mehmet Ali (SCIENDO, 2023)
Jamming is electromagnetic radiation or reflection that impairs the function of electronic instruments and equipment or communication tools. Intentionally disrupting or interfering with GPS signals, which are used for positioning, navigation, and timing, known as GPS jamming, is accomplished using a radio frequency emitting device. On January 8, 2022 (the day of a NATO exercise), it was investigated how GPS signal jamming affected the position accuracy at three IGS points in Iceland. The obtained coordinate differences between kinematic processing and static processing reached values of about 0.5-10 meters for the MAYV, and HOFN stations in this study. In addition to GPS signal jamming effect in Iceland, horizontal and vertical velocity fields of the three IGS stations in Iceland covering a twenty-two year period (2000-2022) in this study. According to the obtained results, a motion of about 2cm-2.5cm per year (horizontal) and 0.1cm-2.1cm per year (vertical) was computed at the three IGS stations (HOFN, REYK, and MAYV) located in Iceland.
Keywords: signal jamming; accuracy; GPS; GNSS; Iceland; motion; SOUTH ICELAND; DEFORMATION; EARTHQUAKES; TRANSFORM; Remote Sensing